2022
DOI: 10.1186/s13045-022-01388-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel tRNA-derived fragment tRF-3022b modulates cell apoptosis and M2 macrophage polarization via binding to cytokines in colorectal cancer

Abstract: AbstracttRNA-derived fragments (tRFs) are a class of small RNAs that occur when tRNAs are broken down by enzymes due to stress. Increasing reports have shown that tRFs are associated with multiple physiological and pathological processes, especially in cancers; however, very little is known of the effects and mechanisms of tRFs. Therefore, further investigation on the biological roles and clinical value of tRFs is required. In this study, we utilized whole-transcriptome sequencing to profile tRFs expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Due to their broad range of functions in post-translational regulation and the haematopoietic microenvironment, sncRNAs, especially miRNAs, play major roles in maintaining haematopoietic stem cell homeostasis and are well-documented in leukaemia progression, metastasis, and drug resistance [46][47][48][49]. Many studies over the past decades have identified non-canonical sncRNAs such as tsRNAs, rsRNAs, and ysRNAs and revealed their versatile roles in cell homeostasis and disease [35,[50][51][52][53][54][55]. To our knowledge, this study is the first to comprehensively characterize the sncRNA profiles of human blood serum and bone marrow supernatant from people with and without AML, revealing a specific sncRNA profile in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their broad range of functions in post-translational regulation and the haematopoietic microenvironment, sncRNAs, especially miRNAs, play major roles in maintaining haematopoietic stem cell homeostasis and are well-documented in leukaemia progression, metastasis, and drug resistance [46][47][48][49]. Many studies over the past decades have identified non-canonical sncRNAs such as tsRNAs, rsRNAs, and ysRNAs and revealed their versatile roles in cell homeostasis and disease [35,[50][51][52][53][54][55]. To our knowledge, this study is the first to comprehensively characterize the sncRNA profiles of human blood serum and bone marrow supernatant from people with and without AML, revealing a specific sncRNA profile in AML.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most abundant small RNA entities, tRNAs and their derivatives, which take part in the pathogenic process of cancer, have attracted broad attention [ 26 ]. An increasing number of studies have reported that tsRNAs contribute to the occurrence and development of diverse cancers such as pancreatic cancer [ 14 ], breast cancer [ 27 ], non-small cell lung cancer [ 28 ], and colorectal cancer [ 29 ], etc. In addition, many studies have indicated that serum tsRNA could serve as a novel biomarker for the diagnosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ren et al found that Schwann cell-derived exosomal MFG-E8 modified macrophage/microglial M2 polarization for attenuating inflammation in spinal cord injury [ 48 ]. Lu et al found that a novel tRNA-derived fragment tRF-3022b modulates M2 macrophage polarization contribute to colorectal cancer progression [ 49 ]. Liu et al found that hepatocyte-derived exosomal miR-192–5p plays a critical role in the activation of M1 macrophages polarization and disease progression of nonalcoholic fatty liver disease (NAFLD) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%